Using EGRA for an Early Evaluation of Two Innovations in Basic Education in Timor-Leste : The New Curriculum and the Professional Learning and Mentoring Program - World Bank (World Bank, Dili, 2020)
This report describes the findings from an educational evaluation carried out in Timor-Leste early in the school year of 2017. The primary purpose of the evaluation was to develop preliminary insights into the effectiveness of the New Curriculum and a second supporting educational innovation, the Professional Leadership and Mentoring Program (PLMP). As such the report addresses the findings of the evaluations regarding improved student learning and relevant school and contextual factors. The objective is to gauge if these two interventions indicate the ability to have some kind of positive impact on educational quality, and if so to help identify areas where these interventions can be intensified. It needs to be noted that both innovations are broad and structural in nature with the potential to have a pervasive impact on the quality of basic education in Timor-Leste.